EXPOSING E-PROCUREMENT FAILURES IN PREVENTING PROCUREMENT OF GOODS AND SERVICES FRAUD - Saputra, Edwin; Anis Chariri (Universitas Tidar, 2023)
This study aims to reveal the failure of e-procurement in preventing fraud in the procurement of goods/ services and to explore the essence of meaning behind these fraudulent practices and behaviors. The method used is a qualitative approach using a interpretive phenomenological lens. Data collection involved in-depth interviews with a semi-structured approach to eight informants and analysis of organization documents. Data analysis using a model modified by Sanders. The findings show that the root of the problems in the procurement of goods/ services are political patronage practices and violations of procurement ethics. The procurement budget is likened to a